Long‐term effectiveness of epidural steroid injections after new episodes of low back pain in older adults. (29th May 2022) - Curatolo, Michele; Rundell, Sean D.; Gold, Laura. S.; Suri, P.; Friedly, Janna L.; Nedeljkovic, Sdrj S.; Deyo, Richard A.; Turner, Judith A.; Bresnahan, Brian W.; Avins, Andrew L.; Kessler, Larry; Heagerty, Patrick J.; et al.
Abstract: Background: There is limited research on the long‐term effectiveness of epidural steroid injections (ESI) in older adults despite the high prevalence of back and leg pain in this age group. We tested the hypotheses that older adults undergoing ESI, compared to patients not receiving ESI: (1) have worse pain, disability and quality of life ('outcomes') pre‐ESI, (2) have improved outcomes after ESI and (3) have improved outcomes due to a specific ESI effect. Methods: We prospectively studied patients ≥65 years old presenting to primary care with new episodes of back pain in three US healthcare systems (BOLD registry). Outcomes were leg and back pain intensity, disability and quality of life, assessed at baseline and 3‐, 6‐, 12‐ and 24‐month follow‐ups. We categorized participants as: (1) ESI within 6 months from the index visit ( n = 295); (2) no ESI within 6 months ( n = 4809); (3) no ESI within 6 months, propensity‐score matched to group 1 ( n = 483). We analysed the data using linear regression and Generalized Estimating Equations. Results: Pain intensity, disability and quality of life at baseline were significantly worse at baseline in ESI patients (group 1) than in group 2. The improvement from baseline to 24 months in all outcomes was statistically significant for group 1. However, no statistically significant differences were observed between outcome trajectories for the propensity‐score matched groups 1 and 3. Conclusions: Older adults treated with ESI have long‐term improvement. However, the improvement is unlikely the result of a specific ESI effect. Significance: In this large, two‐year, prospective study in older adults with a new episode of low back pain, back pain, leg pain, disability and quality of life improved after epidural steroid injections; however, propensity‐score matching revealed that the improvement was unlikely the result of a specific effect of the injections, indicating that epidural steroids are unlikely to provide long‐term benefits in older adults with new episodes of back and leg pain.